Light on peacemaking : a guide to appropriate dispute resolution and mediating family conflict - DiGrazia, Thomas. (Business law collection., 2016)
Many books have been written about the practice of peacemaking, and few, if any, contribute to the non-violent, spiritual side of this ancient science, discipline, practice and art form. This book speaks to that lack and explores the spiritual, non-violent element in peacemaking as it applies to appropriate dispute resolution and mediating family law disputes. Universities will find the book helpful as a textbook in their peacemaking and mediation degree and certificate programs. This book is intended for the professional peacemaker, mediator, lawyer, law student, conciliator, and dispute neutral. Everyday people wishing to improve their own communication skills and strengthen their primary relationships will profit greatly from this book. Those in the family law field, will find much benefit from the peacemaking processes, family counseling psychology, Eastern philosophy and Yoga, collected wisdom, experience and practice pointers presented in Light on Peacemaking. Mental health family practitioners, who are often called upon to act as default, if not, formal mediators and neutrals, will find useful the mediation and peacemaking experiences, techniques and literature related here. Light on Peacemaking also offers the Yoga practitioner a very practical avenue, through example in the legal field, for engaging in seva or service to humanity.